Biologia reprodutiva e presença de cromossomo B em Astyanax scabripinnis (Teleostei: Characidae) - Cornelio, Diana (2013)
Astyanax scabripinnis is a species found in the neotropics, this species forms demes isolated populations in headwater streams. It is taxonomically unresolved, but is presented as an interesting model to study the presence of chromosomal B. The occurrence of these chromosomes in A. scabripinnis may be associated with various environmental factors and population, although little savvy about maintaining parasitic or possible heterotic effects of these chromosomes. The reproductive biology related to the presence of B chromosomes in A. scabripinnis never been addressed. Thus, the object of this study was to investigate whether aspects of the reproductive process, fundamental to the adaptive value may be related to the presence of B chromosomes in A. scabripinnis. Samples were collected quarterly between the years 2012 and 2013 in Campos do Jordao, Sao Paulo, Brazil (22 ° 40 '49.5 "S, 45 ° 23` 31.9 "W) at Stream Farm Lavrinha basin of the Paraíba do Sul. The gonads were classified macroscopically and microscopically second stages of development. Settled seasonally sex ratio of the population in the different samples. We calculated the gonadosomatic ratio (GSR) and the relationship hepatossomática (RHS) separately for females with and without chromosome B. The presence of B chromosomes was confirmed by classical cytogenetic and molecular with the use of chromosome specific probe B constructed by chromosome microdissection and amplification Degenerated Oligonucleotids Primers (DOP-PCR) and subsequent in situ hybridization (FISH). Geometric morphometric analysis were performed separately for males and females with and without the presence of chromosomes B. The results indicate that the sex ratio varied seasonally having an increased number of males compared to females. Hermaphrodite individuals were found at a frequency of 7.7%. The reproductive period is characterized by an atypical reproductive peak during the winter period, beyond the period observed pattern from the spring in September. The presence of B chromosomes has been linked to possible reproductive strategies in different populations studied, especially in relation to energy intake and stages of gonadal development. There morphometric differences both between individuals female and male subjects with and without chromosome B.